Quantifying the spatial and temporal variation in dose from external exposure to radiation: a new tool for use on free-ranging wildlife. (July 2015) - Hinton, Thomas G.; Byrne, Michael E.; Webster, Sarah; Beasley, James C.
Abstract: Inadequate dosimetry is often the fundamental problem in much of the controversial research dealing with radiation effects on free-ranging wildlife. Such research is difficult because of the need to measure dose from several potential pathways of exposure (i.e., internal contamination, external irradiation, and inhalation). Difficulties in quantifying external exposures can contribute significantly to the uncertainties of dose-effect relationships. Quantifying an animal's external exposure due to spatial–temporal use of habitats that can vary by orders of magnitude in radiation levels is particularly challenging. Historically, wildlife dosimetry studies have largely ignored or been unable to accurately quantify variability in external dose because of technological limitations. The difficulties of quantifying the temporal–spatial aspects of external irradiation prompted us to develop a new dosimetry instrument for field research. We merged two existing technologies [Global Positioning Systems (GPS) and electronic dosimeters] to accommodate the restrictive conditions of having a combined unit small enough to be unobtrusively worn on the neck of a free-ranging animal, and sufficiently robust to withstand harsh environmental conditions. The GPS–dosimeter quantifies the spatial and temporal variation in external dose as wildlife traverse radioactively contaminated habitats and sends, via satellites, an animal's location and short term integrated dose to the researcher at a user-defined interval. Herein we describe: (1) the GPS–dosimeters; (2) tests to compare their uniformity of response to external irradiation under laboratory conditions; (3) field tests of their durability when worn on wildlife under natural conditions; and (4) a field application of the new technology at a radioactively contaminated site. Use of coupled GPS–dosimetry will allow, for the first time, researchers to better understand the relationship of animals to their contaminated habitats and better assess animal responses to the stress of radiological exposures. Highlights: Merged two technologies: Global Positioning Systems (GPS) and Electronic Dosimeters. New instrument determines geographical location and external dose in free-ranging wildlife. Data sent by satellites from the animal to the researcher's computer at defined intervals. GPS–dosimeters were tested in a calibration facility and in the field on wild pigs. GPS–dosimeters will help scientists more robustly determined dose to free-ranging wildlife.